2017
DOI: 10.1039/c7ib00039a
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic analysis of red blood cell deformability as a means to assess hemin-induced oxidative stress resulting fromPlasmodium falciparumintraerythrocytic parasitism

Abstract: Hemolytic anemia is one of the hallmarks of malaria and leads to an increase in oxidized heme (hemin) within the plasma of infected individuals. While scavenger proteins sequester much of the circulating heme, it has been hypothesized that extracellular heme may play a central role in malaria pathogenesis. We have previously developed the multiplex fluidic plunger (MFP) device for the measurement of red blood cell (RBC) deformability. Here, we demonstrate that the measurement of changes in RBC deformability is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
0
20
0
3
Order By: Relevance
“…Alternatively, it has been suggested that debris released from rupture of infected pRBCs leads to destruction of bystander RBCs, which would lead to a fixed ratio of bystander death to pRBC rupture. There are a number of experimental studies that have looked at the role of different host immune responses, such as complement and phagocytes, in mediating accelerated pRBC removal, a number of which may provide some evidence of host responses being involved in the destruction of uninfected RBCs . Exploring these different mechanisms of bystander destruction using modeling could help make sense of the experimental literature on mechanisms and host risk factors associated with severe anemia.…”
Section: Host Control Of Parasite Proliferationmentioning
confidence: 99%
“…Alternatively, it has been suggested that debris released from rupture of infected pRBCs leads to destruction of bystander RBCs, which would lead to a fixed ratio of bystander death to pRBC rupture. There are a number of experimental studies that have looked at the role of different host immune responses, such as complement and phagocytes, in mediating accelerated pRBC removal, a number of which may provide some evidence of host responses being involved in the destruction of uninfected RBCs . Exploring these different mechanisms of bystander destruction using modeling could help make sense of the experimental literature on mechanisms and host risk factors associated with severe anemia.…”
Section: Host Control Of Parasite Proliferationmentioning
confidence: 99%
“…Deformability measurement using microfluidics uses minute amounts of a whole blood or purified RBC/WBC in suspension flowing through a funnel-shaped micro-constriction(s) in a disposable plate. As demonstrated in our previous publications, and discussed in the following section, microfluidics devices are capable of providing reproducible intra-and inter-individual data, detecting oxidatively damaged RBC, identifying changes in RBC deformability consequent to storage, and identifying leukocytes [20][21][22][23][24][25][26][27][28].…”
Section: Microfluidicsmentioning
confidence: 99%
“…As evidenced by the number of publications and patents being generated annually, the promise of microfluidic devices in medicine is seemingly unbounded. One area of particular interest to our laboratories has been in the field of transfusion medicine [20][21][22][23][24][25][26][27][28]. Annually over 100,000,000 units of blood are collected worldwide for transfusion purposes.…”
Section: Utility Of Microfluidics In Transfusion Medicinementioning
confidence: 99%
See 2 more Smart Citations